PIBF1 regulates multiple gene expression via impeding long-range chromatin interaction to drive the malignant transformation of HPV16 integration epithelial cells - Xiaomin Li; Ci Ren; Anni Huang; Yue Zhao; Liming Wang; Hui Shen; Chun Gao; Bingxin Chen; Tong Zhu; Jinfeng Xiong; Da Zhu; Yafei Huang; et al. (Journal of Advanced Research, 2024)
Introduction: Human papillomavirus (HPV) integration can induce gene expression dysregulation by destroying higher-order chromatin structure in cervical cancer. Objectives: We established a 13q22 site-specific HPV16 gene knock-in cell model to interrogate the changes in chromatin structure at the initial stages of host cell malignant transformation. Methods: We designed a CRISPR-Cas9 system with sgRNA targeting 13q22 site and constructed the HPV16 gene donor. Cells were cotransfected, screened, and fluorescence sorted. The whole genome sequencing (WGS) was used to confirm the precise HPV16 gene integration site. Western blot and qRT-PCR were used to measure gene expression. In vitro and in vivo analysis were performed to estimate the tumorigenic potential of the HPV16 knock-in cell model. Combined Hi-C, chromatin immunoprecipitation and RNA sequencing analyses revealed correlations between chromatin structure and gene expression. We performed a coimmunoprecipitation assay with anti-PIBF1 antibody to identify endogenous interacting proteins. In vivo analysis was used to determine the role of PIBF1 in the tumor growth of cervical cancer cells. Results: We successfully established a 13q22 site-specific HPV16 gene knock-in cell model. We found that HPV integration promoted cell proliferation, invasion and stratified growth in vitro, and monoclonal proliferation in vivo. HPV integration divided the affected topologically associated domain (TAD) into two smaller domains, and the progesterone-induced blocking factor 1 (PIBF1) gene near the integration site was upregulated, although PIBF1 was not enriched at the domain boundary by CUT-Tag signal analysis. Moreover, PIBF1 was found to interact with the cohesin complex off chromatin to reduce contact domain formation by disrupting the cohesin ring-shaped structure, causing dysregulation of tumorigenesis-related genes. Xenograft experiments determined the role of PIBF1 in the proliferation in cervical cancer cells. Conclusion: We highlight that PIBF1, a potential chromatin structure regulatory protein, is activated by HPV integration, which provides new insights into HPV integration-driven cervical carcinogenesis.